Oceana, or, England and her colonies - Froude, James Anthony (Adam Matthew Digital, 1886)
A personal account of the condition of the British Empire in the late nineteenth century including descriptions of deteriorating relations in South Africa, suggestions that colonial conflict could be reduced by stricter colonial rule, and criticism of the Maori